2018
DOI: 10.1371/journal.pone.0198978
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum retention motif fused to recombinant anti-cancer monoclonal antibody (mAb) CO17-1A affects mAb expression and plant stress response

Abstract: The endoplasmic reticulum (ER) is the main site of protein synthesis, folding, and secretion to other organelles. The capacity of the ER to process proteins is limited, and excessive accumulation of unfolded and misfolded proteins can induce ER stress, which is associated with plant diseases. Here, a transgenic Arabidopsis system was established to express anti-cancer monoclonal antibodies (mAbs) that recognize the tumor-associated antigen GA733-2. Monoclonal antibody (mAb) CO17-1A recognize a tumor-associated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 29 publications
(31 reference statements)
4
23
0
Order By: Relevance
“…The higher purification efficiency of both antibodies might be due to the effect of the C-terminal-fused ER retention motif KDEL. Previous studies prove that mAbs were not retained in the ER in the absence of an ER retention motif [ 25 , 26 , 47 , 48 , 49 ]. They indicated that a protein fused with the KDEL motif at the C-terminal end is retained in the ER or is returned to the ER and its production levels are also improved [ 2 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher purification efficiency of both antibodies might be due to the effect of the C-terminal-fused ER retention motif KDEL. Previous studies prove that mAbs were not retained in the ER in the absence of an ER retention motif [ 25 , 26 , 47 , 48 , 49 ]. They indicated that a protein fused with the KDEL motif at the C-terminal end is retained in the ER or is returned to the ER and its production levels are also improved [ 2 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that a protein fused with the KDEL motif at the C-terminal end is retained in the ER or is returned to the ER and its production levels are also improved [ 2 , 50 , 51 , 52 ]. The ER is a vast subcellular location for the accumulation of proteins that do not require the proteolytic process found in the secretory pathway of intracellular and extracellular spaces [ 23 , 24 , 25 , 26 , 28 , 53 , 54 ]. The figure of Immunoblot analysis to confirm the purified fraction of mAb 13F6-FULL from transgenic N. tabacum plants for Figure 4 A was included as a Figure S2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that mAb P COK expressed in tobacco plants suppressed cancer cell proliferation and changed the expression pattern of certain gangliosides, such as GD1a and GM1, in colorectal cancer cells (Ryu et al 2013). A previous study has reported that anti-cancer mAbs produced by transgenic Arabidopsis plants specifically recognize the tumor-associated antigen GA733-2 (Song et al 2018). In this study, we investigated the bioactivity of mAb P COK expressed in transgenic Arabidopsis plants on anti-cancer effects and the expression change of glycosphingolipid in breast carcinoma, not colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA fragments encoding a heavy chain (HC) fused to the ER retention signal KDEL (HCK) and light chain (LC) of anti-colorectal cancer mAb CO17-1AK have been successfully cloned to a pBI COK vector ( Fig. 1A) (Song et al 2018). Agrobacterium-mediated plant transformation was conducted to generate transgenic Arabidopsis lines expressing mAb CO17-1AK as previously described (Paris et al 2002).…”
Section: Preparation Of Plant Materialsmentioning
confidence: 99%